Le viol : un crime spécifique. Quelques pistes de réflexions issues de l’anthropologie - Véronique Nahoum-Grappe (Criminocorpus)
This article attempts to define 'wartime' rape from a social science rather than a legal point of view: the term is a cliché that needs to be deconstructed in order to better describe the facts: the 'systematic rapes' committed in the former Yugoslavia (1991-95) are different in terms of their political meaning and concrete practice from those more conventionally described as rewards and spoils for warriors in the event of military victory. Moreover, 'wartime rape' needs to be placed in its historical context, and also in terms of the situation in real time. These sexual crimes must then be seen as torture in a situation of impunity, in a logic of domination; they are crimes of defilement where shame and guilt fall on the side of the victim and whose deliberate political use as a tactic designed to destroy the social fabric of the enemy civilian population needs to be investigated in a specific way (as for example currently in the war in Ukraine (2022-20??).